Induction of transplantation tolerance through regulatory cells: from mice to men. Issue 1 (March 2014) - Ferrer, Ivana R.; Hester, Joanna; Bushell, Andrew; Wood, Kathryn J.
Summary: Organ transplantation results in the activation of both innate and adaptive immune responses to the foreign antigens. While these responses can be limited with the use of systemic immunosuppressants, the induction of regulatory cell populations may be a novel strategy for the maintenance of specific immunological unresponsiveness that can reduce the severity of the detrimental side effects of current therapies. Our group has extensively researched different regulatory T‐cell induction protocols for use as cellular therapy in transplantation. In this review, we address the cellular and molecular mechanisms behind regulatory T‐cell suppression and their stability following induction protocols. We further discuss the use of different hematopoietically derived regulatory cell populations, including regulatory B cells, regulatory macrophages, tolerogenic dendritic cells, and myeloid‐derived suppressor cells, for the induction of transplantation tolerance in light of new clinical trials developing therapies with some of these populations.